Revisiting Methodology of Qur’anic Interpretation: A Thematic Contextual Approach to the Qur’an - Kusroni, Kusroni; Zamzami, Mukhammad (Mutawatir : Jurnal Keilmuan Tafsir Hadith, 2021)
Abstract: This article is aimed to propose a methodological interpretation of the Qur’an with reference to the thematic method. The concept is derived from combining the contextual approach with the thematic method of Qur’anic interpretation. Here, I argue that the contextual approach is relevant to develop the existing thematic tafsir methods that are vastly adopted, mostly among the works of college students in Indonesian Islamic universities. Besides, the approach becomes important in its ability to come up with fresh researches in the tafsir studies, as well as to address challenges and socio-religious problems in contemporary society. Therefore, this article attempts to elaborate one of the contemporary approaches introduced by Abdullah Saeed, which he called the contextual approach. By adopting this approach, thematic tafsir will be more comprehensive, as the object of analysis is not limited to text, of the Qur’anic verses and its commentaries, but also the socio-historical context of the studied verses. Abstrak: Artikel ini bertujuan untuk menawarkan kajian metodologis dalam diskursus tafsir al-Qur’an, yaitu metode tematik. Tawaran tersebut berasal dari penggabungan pendekatan kontekstual dengan metode tafsir tematik. Di sini, penulis berpendapat bahwa pendekatan kontekstual sangat relevan untuk mengembangkan metode tafsir tematik yang telah ada dan banyak diadopsi dalam karya-karya akademik di perguruan tinggi keislaman Indonesia. Selain itu, pendekatan ini menjadi penting dalam kemampuannya untuk menghasilkan penelitian-penelitian baru dalam studi tafsir, serta untuk menjawab tantangan dan masalah sosial-keagamaan dalam masyarakat kontemporer. Oleh karena itu, artikel ini mencoba mengelaborasi salah satu pendekatan kontemporer yang diperkenalkan oleh Abdullah Saeed, yang disebutnya sebagai pendekatan kontekstual. Dengan mengadopsi pendekatan ini, tafsir tematik akan lebih komprehensif, karena objek analisisnya tidak terbatas pada teks, yaitu ayat-ayat al-Qur’an dan tafsirnya, tetapi juga konteks sosio-historis dari ayat-ayat yang dikaji.